The Designing Criteria and Sub-Criteria of University Balance Scorecard Using Analytical Hierarchy Process Method - Abadi, Satria; Widyarto, Setyawan (International Journal of Engineering and Technology, 2018)
Universities have an important role in determining the progress and prosperity of a nation. In connection with this progress, the social demand for accountability of higher education also emerged broadly, therefore, the college should be able to compete to improve the quality of all aspect's college business strategy both internally and externally. A university accountability can be seen from the performance measurement of the college, the aim of this study is to design sub-criteria and of performance measurement of a university to improve the quality of higher education in the district Pringsewu Lampung. The design will use the Balanced Scorecard and Analytical Hierarchy Process. Balance Scorecard method is a method that has the ability to analyse leading indicators and lagging indicators. Lagging indicators consist of a financial perspective while Leading indicators consist of the internal business process, learning and growth, customer. While Analytical Hierarchy process is a method that determines the best alternative amongst the chosen criteria and sub-criteria will be ranked, started from the highest score, thus, it will become benchmark percentage to determine the value range from the highest to the lowest. The criteria and sub-criteria of this study are the four main criteria taken the perspective of balance scorecard, Internal Business, Customer, financial, Learning and Growth, whereas, the 9 sub-criteria used to measure the performance are taken from higher education in the region Pringsewu.Â Â